Preparation method of olefin polymerization catalyst component, catalyst system and application of catalyst system
By adding long-chain α-olefin compounds before the spherical catalyst precipitation, the problems of low catalyst activity and low polymer bulk density are solved, and efficient catalyst preparation and production costs are achieved.
Patent Information
- Application Number
- CN202311386674.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-24
AI Technical Summary
In the prior art, when preparing spherical catalysts, the catalyst activity is not high, the polymer bulk density is relatively low, and the process is complicated, which increases production costs.
The long-chain α-olefin compound is added before the spherical solid is precipitated, and spherical catalyst particles with a large average particle size are prepared by adjusting the process steps and conditions.
The activity of the catalyst and the polymer bulk density are improved, the process flow is simplified, and the production cost is reduced.
Smart Images

Figure CN119874968A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of olefin polymerization catalysts, and in particular to a preparation method of an olefin polymerization catalyst component, a catalyst system and applications thereof. Background Art
[0002] Dissolution precipitation is one of the main preparation methods of polyolefin Ziegler-Natta catalysts. This method usually requires the preparation of a homogeneous solution containing a magnesium compound, which is then reacted with a chlorinating agent to precipitate a solid titanium / magnesium complex, and loaded with an internal electron donor compound to form a catalyst component. The characteristic of this method is that the carrier is no longer prepared separately during the catalyst preparation process, but the titanium / magnesium catalyst or catalyst intermediate is precipitated from the solution by co-crystallization. Since the morphology and particle size distribution of this type of catalyst are controlled by the crystallization precipitation process, there are many influencing factors, so the catalyst particle morphology is difficult to control. Early patent documents such as CN85100997A and CN1097597C precipitate particle-type catalysts with wide particle size distribution and poor particle shape. In recent years, the use of emulsification molding process to prepare spherical catalysts has attracted more and more attention. Patent documents CN103619475B and CN107207657A control the crystallization process by emulsification technology, and spherical solids are precipitated, and the morphology has been greatly improved. However, this technology often has low catalyst activity and low polymer bulk density when preparing catalysts with larger average particle size. The methods described in patent documents CN114426597A, CN116041578A and CN116041579A often need to use white oil as an inert dispersion medium, which will increase the difficulty of solvent recovery and treatment. When hexane or decane is used as an inert dispersion medium, the inert dispersion medium needs to be mixed with a titanium-containing compound first, and then contacted with a magnesium-containing solution. The preparation process is complicated and is not conducive to industrial amplification. The method described in patent document CN116041584A needs to consume a large amount of toluene and titanium tetrachloride when preparing large-particle catalysts, and the production cost is high. Summary of the invention
[0003] In view of the problems existing in the above-mentioned prior art, the inventors have found through a large number of experiments that by adding a long-chain α-olefin compound before the spherical solid is precipitated, the resulting catalyst particles have a larger average particle size, have excellent activity when used for propylene polymerization, and have a higher polymer bulk density.
[0004] One of the objects of the present invention is to provide a method for preparing a spherical catalyst component, comprising the following steps:
[0005] S1. contacting a magnesium compound, an organic epoxy compound, an organic phosphorus compound and an inert dispersion medium in an organic solvent to form a magnesium-containing solution;
[0006] S2. In the presence of a precipitation aid and optionally a surfactant, contacting the magnesium-containing solution with a titanium-containing compound to form a mixture;
[0007] S3. The mixture is heated to precipitate a spherical solid, which is filtered, washed and dried to obtain a spherical catalyst component;
[0008] wherein, before the spherical solid is precipitated, a long-chain α-olefin compound as shown in formula (I) is added;
[0009] CH2=CHR a Formula (I)
[0010] Among them, R a It is selected from a straight chain or branched chain alkyl group having 8 to 30 carbon atoms, and a cycloalkyl group having 8 to 30 carbon atoms.
[0011] Optionally, the long-chain α-olefin compound is selected from one or more of the following compounds: 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene, 1-eicosene.
[0012] In the preparation method of the present invention, the long-chain α-olefin compound can be added at any position before the spherical solid is precipitated, and can be added as a whole at one time or in parts multiple times. Specifically, it can be added as a whole or in part during or after the magnesium-containing solution is formed, and can be added as a whole or in part before the mixture is heated to 50°C.
[0013] Optionally, the general formula of the magnesium compound of the present invention is MgX2, wherein X is a halogen, preferably bromine, chlorine or iodine; specifically, it can be at least one of magnesium dichloride, magnesium dibromide and magnesium diiodide, preferably magnesium dichloride.
[0014] Optionally, the organic epoxy compound of the present invention is selected from one or more of ethylene oxide, propylene oxide, epichlorohydrin, epichlorohydrin, butylene oxide, butadiene oxide, butadiene dioxide, methyl glycidyl ether and diglycidyl ether, preferably epichlorohydrin.
[0015] Optionally, the organophosphorus compound of the present invention is selected from one or more of trimethyl phosphate, triethyl phosphate, tributyl phosphate, tripentyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite, and benzyl phosphite, preferably tributyl phosphate.
[0016] Optionally, the inert dispersion medium of the present invention is selected from one or more of hexane, heptane, octane, nonane, decane, dodecane, and cyclohexane, preferably one or more of hexane and decane.
[0017] Optionally, the organic solvent of the present invention is an aromatic hydrocarbon compound, specifically one or more of toluene, ethylbenzene, benzene, and xylene, among which toluene is preferred.
[0018] Optionally, the titanium-containing compound of the present invention is at least one selected from titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, tetrabutoxytitanium, tetraethoxytitanium, triethoxytitanium monochloride, diethoxytitanium dichloride and triethoxytitanium monochloride, preferably titanium tetrachloride.
[0019] Optionally, the precipitation aid of the present invention is selected from one or more of acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, methyl ether, ethyl ether, propyl ether, butyl ether, and pentyl ether, preferably phthalic anhydride.
[0020] Optionally, the surfactant of the present invention is selected from at least one of (meth)acrylic acid alkyl ester polymers and (meth)acrylic acid alkyl ester copolymers, and can be a surfactant product with the trademark T602 purchased from any additive company.
[0021] Optionally, in step S1 of the present invention, the contact method for forming the magnesium-containing solution is not particularly limited. The purpose of the contact is to form a uniform solution containing the magnesium element. The contact conditions include: a contact temperature of 10°C to 100°C, preferably 20°C to 80°C, and a contact time of 0.05 to 10 hours, preferably 0.1 to 6 hours.
[0022] Optionally, in step S2 of the present invention, the method of contacting the magnesium-containing solution with the titanium-containing compound to form a mixture is preferably to drop the titanium-containing compound into the magnesium-containing solution.
[0023] Optionally, in step S2 of the present invention, the contact temperature of the titanium-containing compound and the magnesium-containing solution is -35 to 60°C, preferably -20 to 40°C; the contact time is 1 minute to 10 hours, preferably 3 minutes to 7 hours.
[0024] Optionally, in step S2 of the present invention, the mixture formed exists in the form of colloid, two-phase solution, emulsion and other forms.
[0025] Optionally, in step S2 of the present invention, the preparation method further includes using one or more methods such as vibration, stirring, atomization, shearing, etc. to promote uniform dispersion of the mixture.
[0026] Optionally, in step S3 of the present invention, the temperature raising treatment includes: raising the temperature of the mixture to 50-110° C., solidifying and precipitating spherical solids to obtain a suspension, and then stirring the suspension at this temperature or at a higher temperature (not higher than 130° C.) for 10 minutes to 24 hours.
[0027] According to the present invention, the heating process of the mixture is not specifically limited, and any known method can be used for heating, such as slow, step-by-step, fast or programmed heating. The specific heating method should be adjusted according to the specific formula, contact temperature, etc.; and the inventors have found that in the preparation method described in the present invention, when other conditions are the same, different heating processes will affect the particle morphology and particle size distribution of the final catalyst; specifically, a slower heating process can obtain a better particle morphology, conversely, too fast a heating rate will lead to a deterioration of the particle shape; therefore, the time for the mixture heating process can be 1 minute to 36 hours, preferably 3 minutes to 24 hours.
[0028] According to the present invention, after the spherical solid is precipitated from the mixture, the suspension is stirred at a certain temperature for 10 minutes to 24 hours in order to make the crystal form more stable and improve the particle strength.
[0029] According to the present invention, the spherical solids can be washed and dried by means of techniques known in the art.
[0030] In the preparation method of the present invention, the surfactant can be added at any position before the temperature increase treatment in the preparation method, and can be added as a whole at one time or in portions for multiple times.
[0031] Optionally, in the preparation method of the present invention, the temperature for adding the surfactant is 10°C to 100°C, preferably 10°C to 80°C, and more preferably 10°C to 60°C.
[0032] The preparation method of the present invention further includes the addition of an internal electron donor compound. Optionally, the internal electron donor compound can be added at any position after the start of the temperature increase treatment in the preparation method, including being added in whole or in part during the process of solidification and temperature increase of the mixture; being contacted with the internal electron donor compound in whole or in part after the spherical solid is precipitated or after the spherical solid is precipitated and filtered and washed.
[0033] Optionally, the internal electron donor compound is selected from at least one of di-n-butyl phthalate, diisobutyl phthalate, 2,4-pentanediol dibenzoate, 3,5-heptanediol dibenzoate, diethyl 2,3-diisopropylsuccinate, diisobutyl 2,3-diisopropylsuccinate, di-n-butyl 2,3-diisopropylsuccinate, dimethyl 2,3-diisopropylsuccinate, diisobutyl 2,2-dimethylsuccinate, diisobutyl 2-ethyl-2-methylsuccinate, diethyl 2-ethyl-2-methylsuccinate, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, and 9,9-dimethoxymethylfluorene.
[0034] Optionally, in the preparation method of the present invention, the internal electron donor compound is added at a temperature of 10°C to 150°C, preferably 10°C to 100°C.
[0035] Optionally, in the preparation method of the present invention, the contact time between the spherical solid and the internal electron donor compound is 0.05 to 8 hours, preferably 1 to 6 hours.
[0036] Optionally, in the preparation method of the present invention, per mole of magnesium compound, the amount of the organic epoxy compound is 0.1 to 10 moles, the amount of the organic phosphorus compound is 0.1 to 10 moles, the amount of the organic solvent is 0.5 to 40 moles, the amount of the titanium-containing compound is 0.5 to 25 moles, the amount of the precipitation aid is 0.01 to 1 mole, the amount of the internal electron donor compound is 0.01 to 1 mole, and the amount of the long-chain α-olefin compound is 0.01 to 1 mole; preferably, the amount of the organic epoxy compound is 0.4 to 4 moles, the amount of the organic phosphorus compound is 0.8 to 4 moles, the amount of the organic solvent is 2 to 30 moles, the amount of the titanium-containing compound is 1 to 20 moles, the amount of the precipitation aid is 0.04 to 0.4 moles, the amount of the internal electron donor compound is 0.03 to 0.8 moles, and the amount of the long-chain α-olefin compound is 0.05 to 0.5 moles.
[0037] Optionally, in the preparation method of the present invention, the amount of the surfactant used is 0.01 g to 1 g, and the amount of the inert dispersion medium used is 1 g to 150 g per gram of magnesium compound.
[0038] A second object of the present invention is to provide a spherical catalyst component obtained by the above preparation method.
[0039] The third object of the present invention is to provide a catalyst system for olefin polymerization corresponding to the above object, the catalyst system comprising:
[0040] (1) at least one spherical catalyst component selected from the above-mentioned preparation method;
[0041] (2) alkyl aluminum compounds; and
[0042] (3) Optionally, an external electron donor compound.
[0043] Optionally, according to the present invention, the alkyl aluminum compound has the general formula AlR' n X" 3-n The compound shown, wherein R' is selected from hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, in particular an alkyl group, an aralkyl group, an aryl group, etc.; X" is a halogen, and n is an integer of 1 to 3.
[0044] Optionally, the alkylaluminum compound is selected from at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum monohydrogen, diisobutylaluminum monohydrogen, diethylaluminum monochloride, diisobutylaluminum monochloride, sesquiethylaluminum chloride and ethylaluminum dichloride, preferably triethylaluminum and / or triisobutylaluminum.
[0045] According to the present invention, the amount of the alkyl aluminum compound can be a conventional amount in the art. Preferably, the molar ratio of the aluminum element in the alkyl aluminum compound to the titanium element in the catalyst component is 5 to 5000:1, more preferably 20 to 800:1.
[0046] Optionally, according to the present invention, the external electron donor compound is an organosilicon compound having the general formula R" n' Si(OR y ) 4-n' , wherein n' is an integer of 0 to 3, R" is selected from an alkyl group, a cycloalkyl group, an aryl group, a halogenated alkyl group, a halogen group and a hydrogen atom, and R y One selected from the group consisting of an alkyl group, a cycloalkyl group, an aryl group and a halogenated alkyl group.
[0047] Optionally, the external electron donor compound is selected from at least one of trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyltert-butyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dicyclohexyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, methylcyclohexyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, and (1,1,1-trifluoro-2-propyl)-methyldimethoxysilane, preferably methylcyclohexyldimethoxysilane.
[0048] According to the present invention, the amount of the external electron donor compound is not particularly limited. Preferably, the molar ratio of the alkyl aluminum compound to the external electron donor compound is 0.1 to 500:1, preferably 1 to 300:1, and more preferably 3 to 100:1, based on the aluminum content.
[0049] A fourth object of the present invention is to provide an olefin polymerization method corresponding to the above object, the method comprising: contacting one or more olefins with the above catalyst system under olefin polymerization conditions.
[0050] Optionally, at least one of the olefins is an olefin represented by the formula CH2=CHR, wherein R is hydrogen or a C1-C6 straight or branched alkyl group.
[0051] Optionally, the olefin represented by the formula CH2=CHR is one or more of ethylene, propylene, 1-n-butene, 1-n-pentene, 1-n-hexene, 1-n-octene, and 4-methyl-1-pentene.
[0052] Optionally, the olefin is propylene or a copolymer of propylene and other olefins.
[0053] According to the invention, the polymerization of olefins is carried out according to known methods, operating in the liquid phase of the monomer or in the liquid phase of the monomer in an inert solvent, or in the gas phase, or by a combined polymerization process in the gas and liquid phase.
[0054] Optionally, the conditions for olefin polymerization include: a polymerization temperature of 0°C to 150°C, preferably 60°C to 100°C, and a polymerization reaction pressure of 0.1 MPa to 10 MPa, preferably 0.1 MPa to 5 MPa.
[0055] Compared with the prior art, the present invention has at least the following beneficial effects:
[0056] The present invention adds a long-chain alpha-olefin compound before the spherical solid is precipitated, so that spherical catalyst particles with a large average particle size can be prepared, which have excellent activity when used for propylene polymerization, and the polymer has a high bulk density. In addition, the method of the present invention does not need to use high-viscosity white oil as an inert dispersion medium, which is conducive to solvent recovery; does not need to mix the inert dispersion medium with titanium tetrachloride, which simplifies the process flow; can reduce the consumption of solvents and titanium tetrachloride, and reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention. In the accompanying drawings:
[0058] Figure 1 This is a microscopic image of catalyst component A1. DETAILED DESCRIPTION
[0059] The present invention is described in detail below by way of examples, but the protection scope of the present invention is not limited to the following description.
[0060] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be obtained through commercial channels.
[0061] The test method involved in the embodiment of the present invention is as follows:
[0062] 1. Catalyst particle size distribution: measured by Malvern 2000 n-hexane dispersant laser diffraction method;
[0063] 2. The bulk density (BD) of polymers shall be determined according to ASTM D1895-96.
[0064] 3. The isotacticity index (II) of propylene polymer is determined by the heptane extraction method: 2 g of dried polymer sample is placed in an extractor and extracted with boiling heptane for 6 hours, and the residue is dried to constant weight. The ratio of the obtained polymer weight (g) to 2 (g) is the isotacticity.
[0065] Example 1
[0066] (1) Preparation of catalyst components
[0067] In a 1L reactor that has been repeatedly replaced with high-purity nitrogen, 10.8g of anhydrous magnesium chloride, 75.3g of toluene, 10.6g of epichlorohydrin, 46.9g of tributyl phosphate and 116.8g of decane were added in sequence at 60°C, stirred at 300RMP for 2 hours to obtain a magnesium solution. Then 3.6g of phthalic anhydride and 5.7g of T602 were added and maintained at 60°C for another hour. The magnesium solution was cooled to 0°C, stirred to 400RMP, and 190g of titanium tetrachloride was dripped in. After the addition was completed, it was continued for 1 hour. The temperature was gradually raised to 80°C within 3 hours and maintained for 1 hour. Among them, 3.0mL of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane and 3.0mL of 1-octadecene were added when the temperature was raised to 40°C. After filtering the mother liquor, the solid was washed twice with 200mL of toluene. Add 120 mL of toluene and 80 mL of titanium tetrachloride, treat at 110°C for 0.5 hours, and remove the filtrate. Add 120 mL of toluene and 80 mL of titanium tetrachloride, treat at 110°C for 0.5 hours, and remove the filtrate. Repeat the washing with 200 mL of hexane for 4 times, and dry to obtain catalyst component A1 with an average particle size D50 of 46.5 μm. The morphology of catalyst component A1 is as follows Figure 1 shown.
[0068] (2) Propylene polymerization
[0069] In a 5-liter autoclave, after nitrogen is fully replaced, 5 mL of triethylaluminum hexane solution (the concentration of triethylaluminum is 0.5 mmol / mL), 1 mL of cyclohexylmethyldimethoxysilane (CHMMS) hexane solution (the concentration of CHMMS is 0.1 mmol / mL), 10 mL of anhydrous hexane and 10 mg of solid catalyst component A1 are added at room temperature. The autoclave is closed, and 1.0 L of hydrogen and 2.3 L of liquid propylene are added. The temperature is raised to 70°C, and the polymerization reaction is carried out at 70°C for 1 hour. After the reaction is completed, the reactor is cooled and stirring is stopped, and the reaction product is discharged to obtain an olefin polymer.
[0070] Example 2
[0071] (1) Preparation of catalyst components
[0072] The solid catalyst component A2 was prepared by the method of Example 1, except that the addition position of 1-octadecene was changed to adding into the magnesium-containing solution, and the average particle size D50 was 43.1 μm.
[0073] (2) Propylene polymerization
[0074] The polymerization conditions were the same as in Example 1, using solid catalyst component A2. The polymerization data and olefin polymer data are shown in Table 1.
[0075] Example 3
[0076] (1) Preparation of catalyst components
[0077] The solid catalyst component A3 was prepared by the method of Example 1, except that the amount of 1-octadecene added was 6.0 mL and the average particle size D50 was 50.3 μm.
[0078] (2) Propylene polymerization
[0079] The polymerization conditions were the same as in Example 1, using solid catalyst component A3. The polymerization data and olefin polymer data are shown in Table 1.
[0080] Example 4
[0081] (1) Preparation of catalyst components
[0082] The solid catalyst component A4 was prepared by the method of Example 1, except that 5.0 mL of 1-dodecene was used instead of 1-octadecene, and the average particle size D50 was 41.6 μm.
[0083] (2) Propylene polymerization
[0084] The polymerization conditions were the same as in Example 1, using solid catalyst component A4. The polymerization data and olefin polymer data are shown in Table 1.
[0085] Example 5
[0086] (1) Preparation of catalyst components
[0087] The solid catalyst component A5 was prepared by the method of Example 1, except that 158.2 g of hexane was used instead of decane, and the average particle size D50 was 58.1 μm.
[0088] (2) Propylene polymerization
[0089] The polymerization conditions were the same as in Example 1, using solid catalyst component A5. The polymerization data and olefin polymer data are shown in Table 1.
[0090] Comparative Example 1
[0091] (1) Preparation of catalyst components
[0092] The solid catalyst component D1 was prepared by the method of Example 1, except that 1-octadecene was not added, and the average particle size D50 was 43.7 μm.
[0093] (2) Propylene polymerization
[0094] The polymerization conditions were the same as in Example 1, using solid catalyst component D1. The polymerization data and olefin polymer data are shown in Table 1.
[0095] Comparative Example 2
[0096] (1) Preparation of catalyst components
[0097] The solid catalyst component D2 was prepared by the method of Example 5, except that 1-octadecene was not added, and the average particle size D50 was 55.2 μm.
[0098] (2) Propylene polymerization
[0099] The polymerization conditions were the same as in Example 1, using solid catalyst component D2. The polymerization data and olefin polymer data are shown in Table 1.
[0100] Comparative Example 3
[0101] (1) Preparation of catalyst components
[0102] The solid catalyst component D3 was prepared by the method of Example 1, except that the addition position of 1-octadecene was changed to the first titanium treatment, and the average particle size D50 was 44.6 μm.
[0103] (2) Propylene polymerization
[0104] The polymerization conditions were the same as in Example 1, using solid catalyst component D3. The polymerization data and olefin polymer data are shown in Table 1.
[0105] Table 1.
[0106]
[0107]
[0108] It can be seen from the above examples and comparative examples that by adding long-chain α-olefins before the spherical solids are precipitated, the prepared spherical olefin polymerization catalyst component can have higher polymerization activity and a higher polymer bulk density.
[0109] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0110] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a spherical catalyst component, characterized in that: The following steps are involved: S1. contacting a magnesium compound, an organic epoxy compound, an organic phosphorus compound and an inert dispersion medium in an organic solvent to form a magnesium-containing solution; S2. In the presence of a precipitation aid and optionally a surfactant, contacting the magnesium-containing solution with a titanium-containing compound to form a mixture; S3. The mixture is heated to precipitate a spherical solid, which is filtered, washed and dried to obtain a spherical catalyst component; wherein, before the spherical solid is precipitated, a long-chain α-olefin compound as shown in formula (I) is added; CH2=CHR a Formula (I) Among them, R a It is selected from a straight chain or branched chain alkyl group having 8 to 30 carbon atoms, and a cycloalkyl group having 8 to 30 carbon atoms.
2. The preparation method according to claim 1, characterized in that: The long-chain α-olefin compound is added at any position before the spherical solid is precipitated, and the long-chain α-olefin compound is added as a whole at one time or in parts multiple times; And / or, the long-chain α-olefin compound is selected from one or more of 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene ....
3. The preparation method according to claim 1 or 2, characterized in that: The general formula of the magnesium compound is MgX2, wherein X is a halogen, preferably bromine, chlorine or iodine; preferably, the magnesium compound is at least one of magnesium dichloride, magnesium dibromide and magnesium diiodide; and / or, the organic epoxy compound is selected from one or more of ethylene oxide, propylene oxide, epichlorohydrin, epichlorohydrin, butylene oxide, butadiene oxide, butadiene dioxide, methyl glycidyl ether and diglycidyl ether; And / or, the organophosphorus compound is selected from one or more of trimethyl phosphate, triethyl phosphate, tributyl phosphate, tripentyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite, and benzyl phosphite; and / or, the inert dispersion medium is selected from one or more of hexane, heptane, octane, nonane, decane, dodecane and cyclohexane; And / or, the organic solvent is an aromatic hydrocarbon compound, preferably one or more of toluene, ethylbenzene, benzene, and xylene; and / or, the titanium-containing compound is at least one selected from titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetrabutoxide, titanium tetraethoxide, titanium triethoxide monochloride, titanium diethoxide dichloride and titanium triethoxide monochloride; and / or, the precipitation aid is selected from at least one of acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, methyl ether, ethyl ether, propyl ether, butyl ether and pentyl ether; And / or, the surfactant is selected from at least one of (meth)acrylic acid alkyl ester polymers and (meth)acrylic acid alkyl ester copolymers.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step S1, the contact conditions include: a contact temperature of 10°C to 100°C, preferably 20°C to 80°C, and a contact time of 0.05 to 10 hours, preferably 0.1 to 6 hours; And / or, in step S2, the magnesium-containing solution is contacted with the titanium-containing compound to form a mixture by dropping the titanium-containing compound into the magnesium-containing solution; And / or, in step S2, the contact temperature of the titanium-containing compound and the magnesium-containing solution is -35 to 60°C, preferably -20 to 40°C, and the contact time is 1 minute to 10 hours, preferably 3 minutes to 7 hours; And / or, in step S2, the surfactant is added at a temperature of 10°C to 100°C, preferably 10°C to 80°C, and more preferably 10°C to 60°C; And / or, in step S3, the temperature treatment includes: heating the mixture to 50-110°C, solidifying and precipitating spherical solids to obtain a suspension, and stirring the suspension at 50-130°C for 10 minutes to 24 hours; the time for the temperature treatment is 1 minute to 36 hours, preferably 3 minutes to 24 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method further comprises adding an internal electron donor compound, wherein the internal electron donor compound is added at any position after the temperature rise treatment begins; Preferably, the internal electron donor compound is selected from at least one of di-n-butyl phthalate, diisobutyl phthalate, 2,4-pentanediol dibenzoate, 3,5-heptanediol dibenzoate, diethyl 2,3-diisopropylsuccinate, diisobutyl 2,3-diisopropylsuccinate, di-n-butyl 2,3-diisopropylsuccinate, dimethyl 2,3-diisopropylsuccinate, diisobutyl 2,2-dimethylsuccinate, diisobutyl 2-ethyl-2-methylsuccinate, diethyl 2-ethyl-2-methylsuccinate, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, and 9,9-dimethoxymethylfluorene; Preferably, the internal electron donor compound is added at a temperature of 10°C to 150°C, preferably 10°C to 100°C; Preferably, the contact time between the spherical solid and the internal electron donor compound is 0.05 to 8 hours, preferably 1 to 6 hours; And / or, per mole of magnesium compound, the amount of the organic epoxy compound is 0.1 to 10 moles, the amount of the organic phosphorus compound is 0.1 to 10 moles, the amount of the organic solvent is 0.5 to 40 moles, the amount of the titanium-containing compound is 0.5 to 25 moles, the amount of the precipitation aid is 0.01 to 1 mole, the amount of the internal electron donor compound is 0.01 to 1 mole, and the amount of the long-chain α-olefin compound is 0.01 to 1 mole; preferably, the amount of the organic epoxy compound is 0.4 to 4 moles, the amount of the organic phosphorus compound is 0.8 to 4 moles, the amount of the organic solvent is 2 to 30 moles, the amount of the titanium-containing compound is 1 to 20 moles, the amount of the precipitation aid is 0.04 to 0.4 moles, the amount of the internal electron donor compound is 0.03 to 0.8 moles, and the amount of the long-chain α-olefin compound is 0.05 to 0.5 moles; And / or, based on each gram of magnesium compound, the amount of the surfactant used is 0.01 g to 1 g, and the amount of the inert dispersion medium used is 1 g to 150 g.
6. A spherical catalyst component obtained by the preparation method according to any one of claims 1 to 5.
7. A catalyst system for olefin polymerization, characterized in that: The catalyst system comprises: (1) The catalyst component according to claim 6; (2) alkyl aluminum compounds; and (3) Optionally, an external electron donor compound.
8. The catalyst system according to claim 7, characterized in that The alkyl aluminum compound is of the general formula AlR' n X" 3-n The compound shown, wherein R' is selected from hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, preferably an alkyl group, an aralkyl group, or an aryl group; X" is a halogen, and n is an integer of 1 to 3; Preferably, the alkyl aluminum compound is selected from at least one of trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, trioctylaluminum, diethyl aluminum monohydrogenate, diisobutyl aluminum monohydrogenate, diethyl aluminum monochloride, diisobutyl aluminum monochloride, sesquiethyl aluminum chloride and ethyl aluminum dichloride; and / or, the molar ratio of the aluminum element in the alkyl aluminum compound to the titanium element in the catalyst component is 5 to 5000:1, preferably 20 to 800:1; And / or, the external electron donor compound is an organosilicon compound, the general formula of which is R" n' Si(OR y ) 4-n' , wherein n' is an integer of 0 to 3, R" is selected from an alkyl group, a cycloalkyl group, an aryl group, a halogenated alkyl group, a halogen group and a hydrogen atom, and R y One selected from the group consisting of an alkyl group, a cycloalkyl group, an aryl group, and a halogenated alkyl group; Preferably, the external electron donor compound is selected from at least one of trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyltert-butyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dicyclohexyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, methylcyclohexyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, and (1,1,1-trifluoro-2-propyl)-methyldimethoxysilane; And / or, based on the aluminum content, the molar ratio of the alkyl aluminum compound to the external electron donor compound is 0.1 to 500:1, preferably 1 to 300:1, and more preferably 3 to 100:
1.
9. An olefin polymerization method, characterized in that: The method comprises contacting one or more olefins with the catalyst system of claim 7 or 8 under olefin polymerization conditions.
10. The method according to claim 9, characterized in that At least one of the olefins is an olefin represented by the formula CH2=CHR, wherein R is hydrogen or a C1-C6 straight or branched alkyl group; Preferably, the olefin represented by the formula CH2=CHR is one or more of ethylene, propylene, 1-n-butene, 1-n-pentene, 1-n-hexene, 1-n-octene, 4-methyl-1-pentene; Preferably, the olefin is propylene or a copolymer of propylene and other olefins; And / or, the olefin polymerization conditions include: polymerization reaction temperature of 0°C to 150°C, preferably 60°C to 100°C, polymerization reaction pressure of 0.1MPa to 10MPa, preferably 0.1MPa to 5MPa.
Citation Information
Patent Citations
Porous spherical propylene polymerization catalyst and preparation method thereof
CN104231128A
Molar ratio modifications to larger polyolefin catalysts
US20090171044A1
Polyolefin catalysts and method of preparing an olefin polymer
US5135995A